2013
DOI: 10.1148/rg.332125738
|View full text |Cite
|
Sign up to set email alerts
|

Practice Policy and Quality Initiatives: Decreasing Variability in Turnaround Time for Radiographic Studies from the Emergency Department

Abstract: A study was performed to evaluate use of quality improvement techniques to decrease the variability in turnaround time (TAT) for radiology reports on emergency department (ED) radiographs. An interdepartmental improvement team applied multiple interventions. Statistical process control charts were used to evaluate for improvement in mean TAT for ED radiographs, percentage of ED radiographs read within 35 minutes, and standard deviation of the mean TAT. To determine if the changes in the radiology department ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Even those driving initiatives to decrease turnaround time emphasize the dependence on "the professionalism of the radiologists to provide care in a manner they considered safe" (8). The message is clear: Accurate, high-quality reports must take precedence over speed, despite unrelenting financial pressures and high patient or provider expectations.…”
Section: Computing and Reporting Technologies: Opportunities And Riskmentioning
confidence: 99%
“…Even those driving initiatives to decrease turnaround time emphasize the dependence on "the professionalism of the radiologists to provide care in a manner they considered safe" (8). The message is clear: Accurate, high-quality reports must take precedence over speed, despite unrelenting financial pressures and high patient or provider expectations.…”
Section: Computing and Reporting Technologies: Opportunities And Riskmentioning
confidence: 99%
“…The principal contribution of the radiologist to the ED and patient care consists of imaging reports issued promptly and accurately. These reports prevent time loss of patients in the ED and unnecessary crowding (23). One study comparing teleradiology with radiological opinions by telephone showed that in the event of teleradiology being used, the time between imaging being performed and a report issued was less than 34 min (24).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced overall turnaround times may also lead to reduced time to diagnosis with the potential to improve satisfaction among referring providers (11,12). Although we did not formally assess patient satisfaction related to time to schedule an outpatient MR imaging examination during the study period or maintenance phase, there were no obvious negative effects on the department's regularly reported patient satisfaction scores.…”
Section: Lessons For Future Improvementmentioning
confidence: 97%